Antibodies to Glutamic Acid Decarboxylase-65 is Associated with Total Daily Dose of Insulin Requirement in Children with Type 1 Diabetes - Faisal Faisal; Nur Rochmah; Muhammad Faizi; Novina Novina; Erni Nuraeni (The Indonesian Biomedical Journal, 2023)
BACKGROUND: Type 1 diabetes (T1D) mostly occurs due to the destruction of pancreatic beta cells due to autoimmune processes. Diagnosis of T1D can be established by examining the c-peptide levels and the markers of pancreatic autoantibodies, including glutamic acid decarboxylase 65 autoantibodies (GAD-65). However, the association between c-peptide and anti-GAD-65 toward patients’ clinical manifestations needs to be further explored. Hence, the aim of current study was to identify the association of anti-GAD65 with c-peptide and clinical characteristics in children with T1D.METHODS: Case-control study involving 47 T1D children (T1D group) and 41 healthy children (control group) younger than 18 years old was conducted. Secondary data regarding subjects’ demographic characteristics and medical history were collected from subjects, and serum blood was drawn from each subject for the anti-GAD65 and c-peptide measurement. Anti-GAD65 and c-peptide levels were measured using an Enzyme-Linked Immunosorbent Assay (ELISA) methods.RESULTS: Anti-GAD65 antibody was detected in 78.7% T1D group, while only 2.43% were detected in control group subject (p=0.0000). The c-peptide level of T1D group was 0.07±0.19 nmol/L and control group was 1.5±0.77 nmol/L (p=0.0000). The total daily dose of insulin in subjects with positive anti-GAD65 was greater than in the negative anti-GAD65 (p=0.012). The sensitivity and specificity of the anti-GAD65 were 85.4% was 66.7%, respectively.CONCLUSION: The results of this study show that anti-GAD65 was associated with total daily dose of insulin requirement in children with T1D.KEYWORDS: diabetes mellitus, type 1 diabetes, anti-GAD65, c-peptide